Інформаційний менеджмент соціо-комунікативної громадянської науки - Ткаченко, Ірина; Жежнич, Павло (Видавництво Львівської політехніки, 2025)
This paper explores the application of information management approaches to citizen science projects. It examines the unique characteristics of social communication projects and considers social media as a key platform for their implementation under citizen science initiatives.
Keywords: громадянська наука; інформаційний менджмент; соціальні комунікації